2020
DOI: 10.1002/pmh.1499
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐temporal meta‐analysis review of the personality of Chinese military personnel, 1991–2017

Abstract: Objective -The personality of military personnel is an important factor for their mental health. It has been revealed that military personnel's mental health has changed over the past decades. The objective of the present study was to examine the birth cohort changes in the personality of Chinese military personnel. Methods -To examine the birth cohort changes in the personality of Chinese military personnel, a cross-temporal meta-analysis of 53 studies that measured the personality of Chinese military personn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…On the other hand, the psychological aspects of Chinese people changed. For instance, previous cross-temporal meta-analyses showed that personality (Peng and Luo, 2021;Su and Liu, 2021), loneliness (Yan et al, 2014), anxiety (Xin et al, 2010), and mental health (Silin et al, 2015) among Chinese people have changed over time.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the psychological aspects of Chinese people changed. For instance, previous cross-temporal meta-analyses showed that personality (Peng and Luo, 2021;Su and Liu, 2021), loneliness (Yan et al, 2014), anxiety (Xin et al, 2010), and mental health (Silin et al, 2015) among Chinese people have changed over time.…”
Section: Introductionmentioning
confidence: 99%
“…Twenge adopted this approach to examine changes in various psychological variables over time, such as anxiety, self-esteem, and wellbeing (Twenge, 2000 ; Twenge and Campbell, 2001 ; Twenge et al, 2016 ). In China, Xin and Chi ( 2008 ) first introduced this method in detail, and then a large number of scholars carried out a series of studies using this method, all of which found that social changes affected people's psychological status (Xin and Zhang, 2009 ; Xin et al, 2011 ; Yang et al, 2014 ; Su and Liu, 2020 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%